A new type of gasochromic material: conducting polymers with catalytic nanoparticles. Issue 22 (3rd March 2017) - Hu, Chih-Wei; Yamada, Yasusei; Yoshimura, Kazuki
Abstract : The PANI:PSS/PtNPs nanocomposite shows novel gasochromic phenomena after exposing to hydrogen. Abstract : We report the first observation of gasochromism for a material based on a thin film of polyaniline:polystyrene sulfonate/platinum nanoparticles (PANI:PSS/PtNPs). This novel material displayed a significant colour change, from green to pale yellow, when exposed to hydrogen. Our results show that the PtNPs trigger a reductive reaction on the polymer surface. This new mechanism dramatically expands the selection of available gasochromic materials.